Peran Mahkamah Konstitusi Dalam Mewujudkan Negara Hukum Yang Demokratis - Salia, H Erli (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2017)
The Constitutional Court is the state agency that was born after the reform in 1999. Through the changes to the Constitution of 1945, the Constitutional Court is authorized to examineÂ laws (acts) against the Constitution. In addition there are other powers to protect the fundamental rights relating to the constitutional rights of citizens. As a state agency has the authority of the Constitutional Court, among others, as the supreme interpreter of the constitution in addition to realizing the democratic government, the Constitutional Court to act as the guardian of democracy, protection of constitutional rights of citizens and the protection of human rights.Key words: the rule of law, democracy, constitutional court